ENGINEERING CURRICULUM CHANGES IN HIGHER AND TERTIARY EDUCATION: A CASE OF ONE POLYTECHNIC COLLEGE IN ZIMBABWE - Chingara, Remigio; Machibaya, Etwin; Magwani, Alice (International Journal of Research -GRANTHAALAYAH, 2022)
Whist there are abundant studies on the challenges of implementing curricular changes in schools, less information apparently appears to be available on the challenges of implementing the same in engineering at polytechnic colleges in Zimbabwe. To bridge this gap in knowledge, this study sought to analyse the challenges emanating from implementing curriculum changes in engineering at one polytechnic college in Zimbabwe. The aim was to determine how these challenges effected teaching and learning of engineering courses as well as suggesting strategies to enhance the same. The population in this study comprised of all the 107 lecturers in the department of engineering at Harare Polytechnic in Zimbabwe. The study employed the quantitative research methodology and adopted a descriptive survey design. It utilised stratified sampling to select a sample of 74 lecturers from the engineering department. The study utilised a questionnaire with both open-ended and closed-ended questions to gather data. The study revealed that the addition of non-core subjects in the engineering curriculum added more work to the detriment of the core subjects. Lack of lecturer consultation, resources and staff development were among the challenges cited as affecting the effectiveness of teaching and learning of the new engineering curriculum. The study recommends that there be stakeholder engagement and an evaluation of the impact of the intended engineering curriculum changes before their implementation to mitigate against the negative effects of such changes.